Nose-to-brain delivery of temozolomide-loaded PLGA nanoparticles functionalized with anti-EPHA3 for glioblastoma targeting. (1st January 2018) - Chu, Liuxiang; Wang, Aiping; Ni, Ling; Yan, Xiuju; Song, Yina; Zhao, Mingyu; Sun, Kaoxiang; Mu, Hongjie; Liu, Sha; Wu, Zimei; Zhang, Chunyan
Abstract: Glioblastoma is the most common malignant brain tumor. Efficient delivery of drugs targeting glioblastomas remains a challenge. Ephrin type-A receptor 3 (EPHA3) tyrosine kinase antibody-modified polylactide-co-glycolide (PLGA) nanoparticles (NPs) were developed to target glioblastoma via nose-to-brain delivery. Anti-EPHA3-modified, TBE-loaded NPs were prepared using an emulsion-solvent evaporation method, showed a sustained in vitro release profile up to 48 h and a mean particle size of 145.9 ± 8.7 nm. The cellular uptake of anti-EPHA3-modified NPs by C6 cells was significantly enhanced compared to that of nontargeting NPs ( p < .01). In vivo imaging and distribution studies on the glioma-bearing rats showed that anti-EPHA3-modified NPs exhibited high fluorescence intensity in the brain and effectively accumulated to glioma tissues, indicating the targeting effect of anti-EPHA3. Glioma-bearing rats treated with anti-EPHA3-modified NPs resulted in significantly higher tumor cell apoptosis ( p < .01) than that observed with other formulations and prolonged the median survival time of glioma-bearing rats to 26 days, which was 1.37-fold longer than that of PLGA NPs. The above results indicated that anti-EPHA3-modified NPs may potentially serve as a nose-to-brain drug carrier for the treatment of glioblastoma.